An empirical study on the acceptance of CBDC by Indian bankers: A structural equation modelling approach - Kappal, Jyoti Mehndiratta; Parashar, Neha; Mujumdar, Mugdha; Sharma, Rahul; Nair, Praveen G (Asian Economic and Financial Review, 2025)
The purpose of this empirical study is to examine the aspects that are driving factors for the acceptance of central bank digital currency (CBDC) among Indian bankers using a structural equation modeling (SEM) approach. The responses of bankers were collected by a questionnaire, and the data was analyzed using AMOS to understand the relationships between various factors and acceptance of CBDC among Indian bankers. We collected the data from 380 bankers in two cities: Mumbai and Pune. The data was collected using the justified and snowball sampling method used in this research study. The findings show that several factors, including key factors such as Perception of Digital Currency (PDC), Financial Literacy Competency (FLC), Digital Currency Usage (DCU), and Digital Technology and Adoption (DTA), play a significant role in affecting Intention to Use (ITU) CBDC. The study finds a significant positive relationship between all these factors and the intention to use them. The implications of this research study are important for policymakers, central banks, and financial institutions aiming to implement CBDC initiatives and launch CBDC design frameworks. By accepting the factors, participants can make strategies to promote CBDC adoption, address the potential concerns, and leverage the transformative potential of digital currencies in India’s financial ecosystem.